Analisis Yuridis terhadap Akta Hibah Kepada Penerima yang Melebihi 1/3 dan Diduga Palsu (Studi Putusan Nomor 83/pdt.g/2020/pa. Pst) - Daniel Nainggolan; Hasim Purba; Mahmud Mulyadi; Suprayitno (CV Rewang Rencang, 2025)
A gift is a gift of property from one party to another party that is made while the grantor is still alive. To be valid, both the giver and recipient of the gift must be mature and of sound mind, the property donated must belong to the gift giver, and the gift must be done without coercion. In Indonesian positive law, regulations regarding grants are contained in the Compilation of Islamic Law, the Compilation of Sharia Economic Law, and the Civil Code, with provisions similar to Islamic law, but regulated in Article 1682 of the Civil Code. The research method in this study is descriptive with a normative juridical approach. The results of this research are the validity of grants to adopted children that exceed 1/3 of inherited assets Legal protection for heirs against falsification of gift deeds carried out by recipients who claim to be adopted children can be carried out with repressive and preventive protection measures